Biochemical Composition and Shelf Life Study of Mixed Fruit Juice from Orange & Pineapple - Islam, MA; Ahmad, I; Ahmed, S; Sarker, A (Journal of Environmental Science and Natural Resources, 2015)
In present study, fruit juice has been produced in different ratio of pineapple and orange juice. Juices were pasteurized at 97oC for 5 mins and stored for 35 days in PET bottles at refrigerated temperature. The TSS and pH of the different types of juice were found in the range of 7.73 to 8.53 and 4.33 to 4.53 respectively. Maximum acidity (0.785%) and vitamin C (37.1 mg/100 ml) were found in the sample A (in a ratio 1:1). Aerobic plate count was found within the range of (92 x 106 to 233x 106) cfu/ml. The produced juice blends were subjected to chemical and sensory evaluation at one week interval for five weeks storage time. The chemical analysis showed that, there is a gradual decrease in titratable acidity and Vitamin-C along the storage period. TSS and pH increased progressively during storage period. The mean overall acceptability scores of more than 8 for juice samples indicated the commercial scope for manufacturing good and nutritious pineapple juice blended with orange juice. From all the analysis, it can be observed that the juice blend can be kept conveniently for three weeks without preservatives and 28 days with sodium benzoate at the rate of 0.6 mg/L. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22175 J. Environ. Sci. & Natural Resources, 7(1): 227-232 2014